Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1039/b516741h
|View full text |Cite
|
Sign up to set email alerts
|

Soft matter with hard skin: From skin wrinkles to templating and material characterization

Abstract: The English-language dictionary defines wrinkles as ''small furrows, ridges, or creases on a normally smooth surface, caused by crumpling, folding, or shrinking''. In this paper we review the scientific aspects of wrinkling and the related phenomenon of buckling. Specifically, we discuss how and why wrinkles/buckles form in various materials. We also describe several examples from everyday life, which demonstrate that wrinkling or buckling is indeed a commonplace phenomenon that spans a multitude of length sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
791
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 815 publications
(820 citation statements)
references
References 73 publications
(95 reference statements)
19
791
2
1
Order By: Relevance
“…In the curse of these studies it was also found that groove spacing was independent on the bending magnitude initially applied to the foil to produce the surface cracking. This behavior contrasts with the reported behavior of wrinkled PDMS surfaces where wrinkling-related diffraction effects are tightly dependent on the thickness of the stiff films coating the PDMS and on the magnitude of the experienced strain [5][6][7]26,27 . Other studies about cracking of thin films on compliant substrates also reveal that the average inter-crack distance is always inversely proportional to the strain [11][12][13][14] .…”
contrasting
confidence: 90%
“…In the curse of these studies it was also found that groove spacing was independent on the bending magnitude initially applied to the foil to produce the surface cracking. This behavior contrasts with the reported behavior of wrinkled PDMS surfaces where wrinkling-related diffraction effects are tightly dependent on the thickness of the stiff films coating the PDMS and on the magnitude of the experienced strain [5][6][7]26,27 . Other studies about cracking of thin films on compliant substrates also reveal that the average inter-crack distance is always inversely proportional to the strain [11][12][13][14] .…”
contrasting
confidence: 90%
“…When the compression is slightly above the critical strain, the wrinkles are periodic. The wavelength of the wrinkles is determined by a balance between the deformation of the substrate, which favors short wavelengths, and the bending of the film, which favors long wavelengths [1,2] . By controlling the onset and evolution of wrinkles in a number of different material systems, researchers have demonstrated a wide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Wrinkles arise from competition between the elastic bending energy of a stiff skin and the elastic energy of deformation of the soft substrate on which it is supported. [2,3,21] For a skin of thickness h and Young's modulus Y skin supported on a substrate of Young's modulus Y sub , minimization of the overall elastic energy yields an equilibrium wrinkle wavelength of l / h 1/3 h, where h / Y skin /Y sub . [2,3,21] For large compressive stresses, it is known that hierarchical wrinkling can occur because the amplitude of the smaller, first generation wrinkles saturate, forming an effective skin that can undergo a similar wrinkling process with wavelengths l / h eff 1/3 h eff , where h eff and h eff are the parameters corresponding to the new effective skin.…”
mentioning
confidence: 99%